What makes the hedonic experience of a meal in a top restaurant special and retrievable in the long term? Meal-related, social and personality factors. (1st June 2018) - Muñoz, Francisco; Hildebrandt, Andrea; Schacht, Annekathrin; Stürmer, Birgit; Bröcker, Felix; Martín-Loeches, Manuel; Sommer, Werner
Abstract: Knowing what makes a top gastronomy experience unique and retrievable in the long term is of interest for scientific and economic reasons. Recent attempts to isolate predictors of the hedonic evaluation of food have afforded several factors, such as individual and social attributes, or liking/disliking profiles. However, in these studies relevant variables have been examined in isolation without an integrative perspective. Here we investigated 80 guests enjoying a 23-course meal in a top gastronomy restaurant, in groups of four. Our main question concerned the factors driving the overall evaluation of the meal at its conclusion and after three months. To this aim we administered the Big Five Personality Inventory before the meal, dish-by-dish hedonic ratings, and a multi-dimensional Meal Experience Questionnaire (MEQ) at the end of the meal. Hedonic evaluations of the meal were collected immediately after the meal and three months later. Better immediate overall evaluations were predicted by both the number of peaks in dish-by-dish ratings and by positive ratings of the final dish. Both factors and the number of troughs were also critical for the long-term evaluation after three months. The MEQ dimensions overall interest, valence and distraction predicted immediate evaluations, while the long-term evaluations were determined by interest and high scores on the personality traits agreeableness and conscientiousness. High consistency of the hedonic ratings within quartets indicated the relevance of commensality for the meal experience. The present findings highlight the simultaneous relevance of food- and personality-related factors and commensality for a top gastronomy meal experience in the short and long-run. The uncovered relationships are of theoretical interest and for those involved in designing meals for consumers in various settings.